Motivation, Discipline, and Work Environment: COVID-19 Impact on Employee Performance: Dampak Motivasi, Disiplin, dan Lingkungan Kerja pada Kinerja dan Komitmen Karyawan selama Pandemi COVID-19: Studi Analisis Jalur - Melati Rahayu Lestari; Detak Prapanca (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aimed to investigate the effects of motivation, discipline, and work environment on employee commitment and performance in the context of the COVID-19 pandemic. The research sample consisted of 72 respondents from PT Wings Surya Surabaya in Indonesia. Data were collected through a questionnaire, and path analysis was employed for data analysis. The findings revealed that commitment had a positive influence on employee performance during the COVID-19 crisis. Moreover, motivation, discipline, and work environment were significant predictors of work commitment, as evidenced by the t-test results (p < 0.05). This study provides valuable insights into the crucial factors influencing employee performance and commitment in times of crisis, highlighting the need for organizations to prioritize and enhance motivational factors, discipline, and a conducive work environment to foster commitment and ensure optimal employee performance. Highlights: Motivation drives performance: Explore how employee motivation during the COVID-19 pandemic impacts their overall performance and productivity. Discipline fosters commitment: Investigate the role of discipline in maintaining employee commitment and dedication towards work amidst the challenges posed by the pandemic. Work environment influence: Examine how the work environment, whether remote or in-person, influences employee performance and commitment levels during the COVID-19 pandemic. Keywords: Motivation, Discipline, Work Environment, Employee Performance, Commitment